Inventarisasi dan Klasifikasi Bahaya Erosi dengan Sistem Informasi Geografi di Daerah Hulu Waduk Sempor – Gombong - Dwi Priyo Ariyanto; Hery Widijanto (Sains Tanah - Jurnal Ilmu Tanah dan Agroklimatologi, 2012)
Title : Inventorying and Erosion Hazard Clasification by Geographic Information System in Sempor- Gombong Reservoir Upstream Area. Sempor reservoir is located about 5 km northside of Gombong – Kebumen Regency, has decreased of water reservoir volume about 45% in 2002. The aim of this research has established erosion hazard classification in Sempor reservoir upstream area. This research conducted on April until October 2007. The method used explorative descriptive that was began with interpretating of Landsat 7 ETM+ image satellite and continue with field survey. The erosion prediction calculating used Universal Soil Loss Erosion Equation (USLE) based on land unit.The result shows erosion hazard level has dominated by very heavy level with 2,413.84 ha (55.70 %). The erosion hazard index has been dominated by very high class (2,129.45 ha or 49.14 %). High erosion is caused slope factor, especially on land whose very heavy Erosion Hazard Level and high until very high Erosion hazard index. This research give 8 recommendations about soil conservation technical based on soil deep, erosion prediction amount and erosion hazard level.